Differential age-related transcriptomic analysis of ovarian granulosa cells in Kazakh horses - Ren, Wanlu; Wang, Jianwen; Zeng, Yaqi; Wang, Tongliang; Meng, Jun; Yao, Xinkui (Frontiers in Endocrinology, 2024)
The Kazakh horse, renowned for its excellence as a breed, exhibits distinctive reproductive traits characterized by early maturity and seasonal estrus. While normal reproductive function is crucial for ensuring the breeding and expansion of the Kazakh horse population, a noteworthy decline in reproductive capabilities is observed after reaching 14 years of age. In this study, ovarian granulosa cells (GCs) were meticulously collected from Kazakh horses aged 1, 2, 7, and above 15 years old (excluding 15 years old) for whole transcriptome sequencing. The analysis identified and selected differentially expressed mRNAs, lncRNAs, miRNAs, and circRNAs for each age group, followed by a thorough examination through GO enrichment analysis. The study uncovered significant variations in the expression profiles of mRNAs, lncRNAs, miRNAs, and circRNAs within GCs at different stages of maturity. Notably, eca-miR-486-3p and miR-486-y exhibited the highest degree of connectivity. Subsequent GO, KEGG, PPI, and ceRNA network analyses elucidated that the differentially expressed target genes actively participate in signaling pathways associated with cell proliferation, apoptosis, and hormonal regulation. These pathways include but are not limited to the MAPK signaling pathway, Hippo signaling pathway, Wnt signaling pathway, Calcium signaling pathway, Aldosterone synthesis and secretion, Cellular senescence, and NF-kappa B signaling pathway-essentially encompassing signal transduction pathways crucial to reproductive processes. This research significantly contributes to unraveling the molecular mechanisms governing follicular development in Kazakh horses. It establishes and preliminarily validates a differential regulatory network involving lncRNA-miRNA-mRNA, intricately associated with processes such as cell proliferation, differentiation, and apoptosis and integral to the developmental intricacies of stromal follicles. The findings of this study provide a solid theoretical foundation for delving deeper into the realm of reproductive aging in Kazakh mares, presenting itself as a pivotal regulatory pathway in the context of horse ovarian development.